2020
DOI: 10.2147/cmar.s251348
|View full text |Cite
|
Sign up to set email alerts
|

<p>The circ-AMOTL1/ENO1 Axis Implicated in the Tumorigenesis of OLP-Associated Oral Squamous Cell Carcinoma</p>

Abstract: Background: Oral squamous cell carcinoma (OSCC) may develop from a variety of oral potentially malignant disorders, but the mechanism of malignant transformation is still unknown. Among them, oral lichen planus (OLP) has a high prevalence. Previous studies have shown that α-enolase (ENO1) can promote cell proliferation and play an important role in tumorigenesis. In this study, we aim to explore the mechanism of ENO1 regulation in the process of OSCC tumorigenesis from OLP. Methods: ENO1 expression in tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…The present analysis, performed on patients’ surgical resection specimens, showed that overexpression of ENO1 in tumoral cells was significantly correlated with disease advancement, the presence of metastases in regional lymph nodes, and shorter cancer-specific overall survival. Our clinical observations are in line with previously published clinical research on several other human cancers [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Proteomic analysis of peripheral T-cell lymphomas not otherwise specified (PTCL-NOS) revealed a significantly increased ENO1 level (eightfold) in neoplastic cells compared with the non-lymphoma tissue [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…The present analysis, performed on patients’ surgical resection specimens, showed that overexpression of ENO1 in tumoral cells was significantly correlated with disease advancement, the presence of metastases in regional lymph nodes, and shorter cancer-specific overall survival. Our clinical observations are in line with previously published clinical research on several other human cancers [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Proteomic analysis of peripheral T-cell lymphomas not otherwise specified (PTCL-NOS) revealed a significantly increased ENO1 level (eightfold) in neoplastic cells compared with the non-lymphoma tissue [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…As has been demonstrated by an in vitro study, ENO1 may serve as a tumor-promoting gene in oral squamous cell carcinoma through the circ-AMOTL1/miR-22-3p/miR-1294 network. 77 Similarly, long ncRNA (lncRNA) can also directly bind to ENO1 and regulate its translation. lncRNA P5848 can upregulate both gene and protein expression levels of ENO1, promoting cancer cell growth.…”
Section: Eno1 Functions Regulated By Non-coding Rnamentioning
confidence: 99%
“…Oncogenic circRNAs are up-regulated in cancers, promote proliferation, and suppress apoptosis [25][26][27], whereas tumor suppressive circRNAs, as shown for circRNA-102450 in this study, are down-regulated and negatively correlated with cancer progression [28,29]. In OSCC, altered expression of circRNAs has been implicated in carcinogenesis and tumor progression [30,31]; however, the detailed functions and mechanisms of specific circRNAs remain poorly understood.…”
Section: Discussionmentioning
confidence: 78%